Cardiac catheterization and percutaneous intervention procedures on extracorporeal membrane oxygenation support - Guerrero-Miranda, Cesar Y.; Hall, Shelley A. (Annals of Cardiothoracic Surgery; Vol 8, No 1 (January 01, 2019): Extracorporeal Life Support in Refractory Heart Failure, 2018)
Extracorporeal membrane oxygenation (ECMO) is used to support critically ill patients when conventional therapies have failed. ECMO has been available for four decades and has gained use as a rescue therapy in severe refractory hypoxic disorders and in patients with refractory cardiogenic shock (RCS). Over recent years, several percutaneous cardiac interventions and implant devices have been developed that are now used frequently in conjunction with ECMO in order to maintain organ perfusion. Here, we review the literature on VA-ECMO cannulation location, the use of VA-ECMO in interventions (e.g., coronary interventions and structural heart interventions) and percutaneous cardiac device implantation in VA-ECMO recipients with RCS.